An Application of Interval Valued Fuzzy Matrices in Agricultural Field - C. Loganathan; V. Pushpalatha (International Journal of Mathematics And its Applications, 2018)
In this paper, we extend sanchez's approach in agricultural field to find the disease of the plant by using the representation of an interval valued fuzzy matrix as an interval matrix of two fuzzy matrices. We introduce geometric mean of an interval valued fuzzy matrix and propose a method to study sanchez's approach in agriculture field through the geometric mean of an interval valued fuzzy matrix.